Pelatihan Teknis Penggunaan Aplikasi PeduliLindungi Guna Melacak Penyebaran COVID-19 - Fiby Nur Afiana; Ika Romadoni Yunita; Luzi Dwi Oktaviana; Uswatun Hasanah (Universitas Amikom Purwokerto, 2020)
One of the four strategies presented by the Covid-19 Task Force for the Acceleration of Handling to strengthen physical distancing policy as a basic strategy for overcoming the spread of Covid-19 is the tracing of positive cases. Tracing anyone who has contact with patients if done manually requires quite a long time and within that time the virus could have spread very quickly. The Care Concern application issued by the government through the Ministry of Communication and Information Technology (Kominfo) can do tracing quickly through the recording of GPS and Bluetooth that are active on android devices. Through this dedication, participants can understand how technology can help the spread of the covid-19 virus by using the Care Protect Application to trace contacts (tracing), see how the condition of the surrounding environmental zones so that they can take anticipatory and preventive actions. Contact tracing is very helpful in controlling the spread of Covid-19 with a number of precautions taken by the local government if anyone who has contact with a positive Covid-19 patient is known.